2021
DOI: 10.36253/ahsc-9689
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Colocasia esculenta and Xanthosoma mafaffa in Togo, West Africa

Abstract: Taro and new cocoyam are root and leaf crops commonly grown in tropical to warm temperate regions. In Togo, they are neglected and underutilised. Here we report the genetic diversity of 26 accessions of taro and 101 accessions of new cocoyam. Analysis of simple sequence repeats revealed low polymorphic information content of 0.43 and 0.25 in taro and new cocoyam, respectively. PCA scatterplots and Neighbour Joining dendrograms based on the SSR data clustered accessions into groups that more-or-less correspond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, Colocasia varieties (C3, CD) produced more tubers (5 to 6) than Xanthosoma ones (2 to 3, on average). Similar differences were also highlighted for growth and its attributes plant height, diameter of pseudo-stem, petiole length, lamina length, lamina width, leaf area and yield attributes, number of corms, cormels and suckers per plant, cormel weight and yield per plant among Colocasia esculenta, Xanthosoma sagittifolium and Xanthosoma mafaffa genotypes, cultivars or accessions (ReyesCastro et al [34]; Mengistu [35]; Bammite et al [31]; Nwofia et al [36]; Okoli et al [33]).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…On the other hand, Colocasia varieties (C3, CD) produced more tubers (5 to 6) than Xanthosoma ones (2 to 3, on average). Similar differences were also highlighted for growth and its attributes plant height, diameter of pseudo-stem, petiole length, lamina length, lamina width, leaf area and yield attributes, number of corms, cormels and suckers per plant, cormel weight and yield per plant among Colocasia esculenta, Xanthosoma sagittifolium and Xanthosoma mafaffa genotypes, cultivars or accessions (ReyesCastro et al [34]; Mengistu [35]; Bammite et al [31]; Nwofia et al [36]; Okoli et al [33]).…”
Section: Discussionmentioning
confidence: 65%
“…Similar observations have also been made by other authors. Thus, Bammite et al [31] observed that plant height is slightly higher in Xanthosoma mafaffa. Touckia et al [32] reported good vegetative growth in Xanthosoma varieties expressed in particular by higher lamina length and width, while in Colocasia, production was better with two to three times more tubers.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, scientists in WA and beyond have been gathering information, developing strategies, and evaluating stress factors to help to improve the taro crop [8,18,19,58,64,[94][95][96][97][98]. Two of the improvements achieved to date are outlined as follows: i.…”
Section: Opportunities For Improved Taro Production In Wamentioning
confidence: 99%
“…This helps to ensure that collection programs are executed using international standard procedures; ii. Characterization of local and exotic germplasm for agro-morphological traits, disease resistance, and nutritional qualities, to be used as the basis for taro improvement: Several authors have used morphological characterization to evaluate taro cultivars, including agromorphological traits, diseases, and flowering ability [58,75,90,97]. This has helped the classification of taro into different morphotypes, which can then be used in taro improvement programs.…”
Section: Opportunities For Improved Taro Production In Wamentioning
confidence: 99%
“…Although generative propagation can occur naturally, its monoculture and hetero-culture vegetative propagation also exist (Habibah and Astika, 2020). Most parts of taro plants are edible, including the tuberous portion, stolon, leaf blades, petioles, and flowers (Bammite et al, 2021). Taro tubers, which contain 70%-80% starch utilized as a staple food instead of rice, ranked ninth among food crops worldwide (Rashmi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%